Benchmarking challenges in facilities management in Nigeria. Issue 2 (5th May 2015) - Adewunmi, Yewande Adetoro; Omirin, Modupe; Koleoso, Hikmot
Abstract : Purpose: – The paper aims to examine benchmarking challenges among Nigerian Facilities management (FM) practitioners. Design/methodology/approach: – Data collection was through self-administered questionnaires sent to 120 FM organizations in Lagos metropolis, 50 in Abuja and 15 in Port Harcourt. Also, interviews were conducted on six facilities managers to ascertain challenges faced by organizations that use best practice benchmarking. The survey achieved a total response rate of 74 per cent in Lagos, 66 per cent in Abuja and 93 per cent in Port Harcourt, respectively. Grand mean scores and relative importance index were used to ascertain ranking of the challenges. One-way analysis of variance and t -test were used to establish whether organizations' characteristics bring about significant differences in the types of benchmarking challenges encountered. Findings: – Overall, the top four challenges of benchmarking were "unwillingness of employees to change", "inadequate understanding of the exercise of benchmarking", "inadequate access to data from other organizations" and "poor execution of-the benchmarking exercise". Also, FM organization location result in a significant difference in benchmarking challenges. Practical implications: – The implication of the study is that it will assist in identifying impediments to benchmarking and barriers faced during benchmarking and, thus, enable recommendations to be made to minimize such challenges. Originality/value: – There are limited empirical studies on the problems of benchmarking in developing countries.